Reservation in Promotion in India: Exploring the Impact of Reservation in Promotion in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian polity has witnessed several critical issues under its development like that of castes untouchably slavery etc. One among those has been reservations in promotion. The following concept turned the entire structure of Indian polity upside down as the same was vehemently opposed by the people of other stratification. Granting of reservation in Promotion seeks to withhold seats in the government office for the socially and economically weaker sections of the society ensuring hem benefit at the time of Promotion The government under the leadership of Narsimha Rao, by inculcating the 77 Constitutional amendment to the Indian constitution under (Art. 16 (4A) initiated the first step towards providing reservations in Promotions Further by virtue of the 85th Constitutional amendment, later on with a view to grant legal status to consequential Promotion the Govt. headed by Dr. Manmohan Singh replaced the Particular section.The issue was not to be dealt single handedly while in chain came several other issues which were to be paid attention too. There were debates that the following provision should also tend to cover not only the SC ST group people but shall also be implemented for the benefit of those falling under the OBC strata[1] There was a Problem in seeking preference amongst the SC ST people particularly in areas where the distribution of the two classes was inappropriate particularly when any candidate is to considered for any govt. Office of highest order also weather the following reservation policy would also seek its place in a private institutions or would it just remained confined or restricted to any Govt. office in consideration